Efektivitas Limbah Tongkol Jagung sebagai Campuran Bahan Dasar Pembuatan Baglog terhadap Percepatan Tumbuh Miselium Jamur Tiram (Pleurotus ostreatus) - Ni Kadek Dwityasari Anggraeni; Ismail Efendi; Baiq Mirawati (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Corn is the second staple food after rice with a large area of cultivation in West Nusa Tenggara Province, especially in Sumbawa Regency, corn production in 2019 reached 697,210 tons, in a harvested area of 110,035 ha, productivity reached 63.36 kw/ha. Until now, corncob waste has not been optimally utilized, because its economic value is very low. The purpose of this study was to determine the effectiveness of corncob waste as a mixture of basic ingredients in making baglog of oyster mushrooms (Pleurotus ostreatus). This type of research is a pure experimental research (true experiment). The research approach used is quantitative. The research design used was Completely Randomized Design (CRD), using 4 treatments and 5 replications, so that 20 treatment replications were obtained. The results showed that the average acceleration of mycelium length growth in different treatments showed significantly different numbers, namely 2.03 cm produced by P3 treatment (25% wood sawdust + 75% corncob powder).